Perancangan Sistem Smart Room dengan Modul NodeMCU ESP8266 Berbasis Internet of Things (IoT) - Dandy; Lasut, Desiyanna (Jurnal Sistem Komputer (SISKOM), 2026)
This design aims to simplify the process of controlling devices such as lights, LED strips, and fans for users in the era of globalization and modern technology. The subject of this research is to ease user interaction with various devices in a room or space. The control system is designed using an Internet of Things (IoT) network based on Arduino, utilizing the BLYNK application and Relay as a switch for the application. A Smart Room is a solution for leveraging technology to create an intelligent space capable of regulating temperature, lighting, and electronic devices automatically. This research evaluates the ability of the technology to meet the needs of modern living spaces and discusses the technical and ethical implications of implementing smart rooms. The results indicate that smart rooms have the potential to simplify life and enhance comfort, but also require consideration of ethical issues and privacy concerns. This study provides direction for the development of better and more responsible smart room technologies.